CONTENT VARIATIONS OF CARBAMAZEPINE TABLETS IN IRAQI COMMUNITY PHARMACIES: APPLICATION OF HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY ASSAY METHOD - Sahib, Mohanad Naji (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Â Objective: There is paucity in the literature and documentation regarding the post-marketing product quality in Iraq and Middle East countries in general. Therefore, a simple reverse phase high-performance liquid chromatography (RP-HPLC) method was developed and validated for the determination of carbamazepine (CMZ) content in post-marketed tablet dosage form. Methods: The RP-HPLC analysis was run at a flow rate of 1 ml/min with a mixture of methanol: water (70:30) mobile phase using a Thermo Synchronise C18 column at a UV detection wavelength of 230 nm. The method was validated for selectivity, linearity, precision, accuracy, limit of detection (LOD), limit of quantification (LOQ), solution stability, and robustness. Results: The calibration curve was linear over a concentration range of 1â€“20 Î¼g/ml (r2=0.9999) with LOD and LOQ of 0.01 and 0.04 Î¼g/ml, respectively. The intraday and interday precision and accuracy were between 0.04â€“1.67% and 0.04â€“0.78%, respectively. The results of analysis of the four brands of CMZ tablets were passed the European Pharmacopoeia specification but with a high standard deviation of mean drug content of some brands. Conclusion: This study shows that the quality of post-marketed drugs and/or the storage conditions in developing countries must be carefully assessed for a better therapeutic response.